A lanthanide MOF with nanostructured node disorder - Sarah L. Griffin; Emily G. Meekel; Johnathan M. Bulled; Stefano Canossa; Alexander Wahrhaftig-Lewis; Ella M. Schmidt; Neil R. Champness (Nature Communications)
Abstract Structural disorder can be used to tune the properties of functional materials and is an important tool that can be employed for the development of complex framework materials, such as metal-organic frameworks. Here we show the synthesis and structural characterization of a metal-organic framework, UoB-100(Dy). Average structure refinements indicate that the node is disordered between two orientations of the nonanuclear secondary building unit (SBU). By performing 3D diffuse scattering (DS) analysis and Monte Carlo (MC) simulations, we confirm the presence of strong correlations between the metal clusters of UoB-100(Dy). These nodes assemble into a complex nanodomain structure. Quantum mechanical calculations identify linker strain as the driving force behind the nanodomain structure. The implications of such a nanodomain structure for the magnetic, gas storage, and mechanical properties of lanthanide MOFs are discussed.